DEVELOPMENT OF GOOGLE SITES-BASED COUNSELING GUIDANCE INFORMATION SERVICES ON BULLYING - Ismanto, Marmi Dwi; Ilham, Ilham; Habibi, Akhmad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2024)
Bullying has begun to occur in schools in big cities and in remote villages. However, many students do not yet realize whether they have experienced bullying or are even the perpetrators of bullying. This development aims to produce guidance and counseling information services that contain material regarding bullying using Google Sites and fulfill the elements of conceptual, theoretical and practical feasibility. Apart from that, this development is also expected to provide an overview of the creation of information media about bullying, as well as assessing the usefulness of the media for students. This research method uses the Research and Development (R&D) method. The development model adapts the ADDIE concept, namely Analysis, Design, Development, Implementation and Evaluation. To assess the validity of this product, a feasibility test was carried out on experts, a media expert feasibility test obtained a percentage of 85.56% and a material expert feasibility test obtained a percentage of 92.5% and a product trial on teachers obtained a result of 83.52% and a product trial on the student got a result of 81.25%. Thus, it can be concluded that this media is suitable for use as an information service for guidance and counseling on bullying.